EVALUASI PERENCANAAN OBAT DI DINAS KESEHATAN KOTA PARIAMAN TAHUN 2010-2011 - , NOVITA NORMASARI, dr.Sulanto Saleh Danu, Sp.FK. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: The supply of drug needs to be managed efficiently in order to prevent all types of wastage including overstocking and expiry. This wastage may influence the quality of health care provided to patient. Planning as one of the drug management functions to be supported by good management support so that the drug are planned according to the needs, targeted and effective. Drug management problems frequently encountered is a generic drug price changes that occur almost every year, dropping buffer stock from the Provincial Health Office nearing expiration, the procurement process is uncertain conditions, drug required are not available in the market and reports that are less accurate, because the HR and computerized systems inadequate. Above problems can affect the planning process. Therefore, it is necessary to evaluate the drug planning in Pariaman District Health Office. Objective: To evaluate the drug planning at Pariaman District Health Office in year 2010-2011 Methods: This study used case study research methods. Subjects of this study are Head of Pariaman District Health Office, Head of P2P Programme, Chief of Farmakmin Section, Head of Pharmaceutical Installation, Head of Planning and Evaluation Programme, Head and Coordinator of Pharmacy in Prymary Health Cares. Qualitative data were collected by in-depth interviews. Quantitative data were collected through observation of documents related to drug plan. and filled stratification instruments of medicine management. Results: Drug planning process in Pariaman District Health Office have not been fully performed in accordance with the guidelines of the Ministry of Health and WHO. Planning is only done by the method of consumption and not the method of morbidity and VEN-ABC analysis. Management support such organizations, budgets and policies are adequate but the SIM and human resources are still inadequate. Indicator for the availability of drugs in 2011 showed that the accuracy of the drug plan in Pariaman DKK in 2010 was 5.1%, the availability of the drug at a rate of 15.3% safe, compliance with medication class were 78.8%, availability of drugs as needed 89%, excess drug 80.0%, 11.0% stock out, 4.7% dead stock and expired amounted to Rp. 49,251,783.92, -. Conclusion: Drug planning process in DKK Pariaman drug is not appropriate. Management support on HR and management information systems are still inadequate. Indicator of the availability of the drug showed high levels of availability of drugs and the number of expired drugs.